Multipotent Mesenchymal Stem Cell Treatment for Discogenic Low Back Pain and Disc Degeneration - Jeffrey Zeckser; Michael Wolff; Jason Tucker; Josh Goodwin (Hindawi Limited, 2016)
Low back pain with resultant loss of function, decreased productivity, and high economic costs is burdensome for both the individual and the society. Evidence suggests that intervertebral disc pathology is a major contributor to spine-related pain and degeneration. When commonly used conservative therapies fail, traditional percutaneous or surgical options may be beneficial for pain relief but are suboptimal because of their inability to alter disc microenvironment catabolism, restore disc tissue, and/or preserve native spine biomechanics. Percutaneously injected Multipotent Mesenchymal Stem Cell (MSC) therapy has recently gained clinical interest for its potential to revolutionarily treat disc-generated (discogenic) pain and associated disc degeneration. Unlike previous therapies to date, MSCs may uniquely offer the ability to improve discogenic pain and provide more sustained improvement by reducing disc microenvironment catabolism and regenerating disc tissue. Consistent treatment success has the potential to create a paradigm shift with regards to the treatment of discogenic pain and disc degeneration.